Experience of ultrasound diagnostics of vascular rings and its influence on surgical treatment - Pavlova, A.; Kurkevych, A.; Rudenko, N.; Ialynska, T.; Yemec, R.; Yemec, I. (Ukrainian Journal of Cardiovascular Surgery, 2018)
Contemporary methods diagnose congenital heart diseases (CHD) with high accuracy but postnatal diagnostics of vascular rings (VR) remains difficult. From 2004 to 2017 in our Center were performed 7740 primary fetal echocardiograms and more than 65,000 echocardiograms for children. From 2004 to 2017 18589 operations of congenital heart disease were performed, of them 95 (0,51%) were VR surgery. Of all patients treated with VR 21 (22,1%) had prenatal diagnosis, 74 (77,9%) – had postnatal. Since 2011 during postnatal and prenatal echocardiography, we introduced a new protocol with necessary views for VR visualization. Thanks to the use it increased the number of operations on the VR. Surgical treatment of VR has excellent results with low surgical risk. For the successful VR surgical treatment is necessary CT to perform for required to clarify the anatomy of the VR and the trachea. Prenatal and postnatal Echo can help of VR detection in a group of asymptomatic patients.